2020
DOI: 10.1590/0074-02760200370
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Bacillus anthracis and Bacillus anthracis-like spores in soil from state of Rio de Janeiro, Brazil

Abstract: BACKGROUND Bacillus anthracis is the aetiologic agent of anthrax, a re-emerging, septicaemic, haemorrhagic and lethal disease that affects humans, domestic ruminants and wildlife. Plasmids pXO1 and pXO2 are attributes that confer pathogenicity to B. anthracis strains. This bacterium was used as biological weapon in the World Wars and in the biological attack in the United States of America at 2001. B. anthracis is classified as a Tier 1 bioterrorism agent by the Centers for Diseases Control and Prevention. Ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…All the investigated bacilli except B. megaterium harboured either cap or pag gene while B. anthracis and B. cereus haboured both the virulence genes. Uneven distribution of these genes among the isolates may suggest the loss or gain of plasmids for virulence among the bacteria as recently reported elsewhere [23]. Bacillus anthracis, is thought to differ from other species of same genus by the presence of the virulence genes borne on the plasmids, pXO1 and pXO2 encoding the lethal toxin genes that cause the severe inhalation anthrax illness.…”
Section: Discussionmentioning
confidence: 67%
“…All the investigated bacilli except B. megaterium harboured either cap or pag gene while B. anthracis and B. cereus haboured both the virulence genes. Uneven distribution of these genes among the isolates may suggest the loss or gain of plasmids for virulence among the bacteria as recently reported elsewhere [23]. Bacillus anthracis, is thought to differ from other species of same genus by the presence of the virulence genes borne on the plasmids, pXO1 and pXO2 encoding the lethal toxin genes that cause the severe inhalation anthrax illness.…”
Section: Discussionmentioning
confidence: 67%
“…Studies of spore-forming bacteria have shown their resistance to chemicals and elevated temperatures. This property can vary both in diverse types of microorganisms and in strains of the same species [13]. It was established that variable sporulation conditions, including the use of liquid or solid media, levels of nutrients and divalent cations, as well as pH and temperature of the sporulation medium, can affect the persistence properties of the resulting spores [14].…”
Section: Introductionmentioning
confidence: 99%
“…However, there is still a signifi cant risk of new outbreaks, mainly due to the large number of old animal burial sites (13,500) and their unresolved current status. It was repeatedly established by researchers from Russia (Dugharzhapova et al, 2016;Shishkova et al, 2011), Albania (Peculi et al, 2015), Brazil (Salgado, 2020) and Italy (Fasanella et al, 2015, that these burial sites of anthrax infected animal carcasses pose a particular risk as natural reservoir of this pathogen. In addition, there are most likely unknown soil foci of the pathogen originating from herding or war (World War II) casualties.…”
Section: Introductionmentioning
confidence: 99%